COGNITIVE BIAS ANALYSIS TERHADAP KINERJA USAHA KECIL DAN MENENGAH (UKM) DENGAN KEPUTUSAN INVESTASI SEBAGAI VARIABEL INTERVENING PADA MASA PANDEMI COVID 19 - Siti Aisyah Hidayati; Sri Wahyulina; Embun Suryani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to analyze the Effect of Cognitive Bias on Company Performance with Investment Decisions as an Intervening Variable in Small and Medium Enterprises (SMEs) on Lombok Island during the Covid 19 Pandemic. The theoretical contribution of this research is expected to contribute to science and theory development behavioral finance related to investment decision making and company performance in Small and Medium Enterprises (SMEs). In addition, it is also expected that behavioral finance will become the subject of discussion in financial management courses. Furthermore, the practical contribution of this research is expected to provide input, suggestions and recommendations to the policy makers of the NTB Provincial Government in making policies related to the development of SMEs. This research is a quantitative approach-based research, with explanatory research as the type of research. The research population is all SMEs on the island of Lombok. The sampling technique was carried out using non-probability sampling, namely using judgment sampling, namely selecting SMEs engaged in the pottery industry and already exporting. From the existing population, there are 34 (thirty four) SMEs that can be taken as samples. Respondents in this study are the owners of each of these SMEs. The data collection technique used in this study was a questionnaire. In order to achieve the research objectives and to test the hypothesis, the data obtained will be processed as needed using the GSCA (Generalized Structured Component Analysis) statistical tool. The results of the study show that Cognitive Bias have a positive and significant effect on company performance. The decision to place funds for working capital does not intervene with Cognitive Bias on Company Performance in Small and Medium Enterprises (SMEs) on Lombok Island during the Covid 19 Pandemic. Most of them have high school and university education and the length of business is more than 15 (fifteen) years.